Implementasi Teknologi Informasi dalam E-Commerce Menuju MEA (Masyarakat Ekonomi Asean) - Agus Tedyyana (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
The background of this research is the development of information technology to the 2015 ASEAN Economic Community (AEC). Efforts of government and business to improve the competitiveness of production processes, and offering and exchanging products of value to others, while also forming ability of traditional economic sectors and equitable development. One form of the urban market preferred form via the internet market, commonly called e-business or e-commerce as well. E-commerce activities to enable people to make buying and selling at online stores, popularly called online shop. The emergence of online trading causes a wide range of products can be seen and known the price, even Negotiate the price without having to come directly to where the goods are sold. The goal in this research is to analyze how the implementation of information technology in e-commerce online shop to the AEC on Shafiyahijab Syar’i. This research uses the case study method.The results showed the ASEAN Economic Community (AEC) provides opportunities for businesses, including small and medium enterprises to go ASEAN. In the face of AEC, improving the competitiveness of businesses can be done through the implementation of information technology such as the development of e-commerce. With e-commerce, the ASEAN community can interact in business activities without being confined space and distance. For example the business activities developed by the online shop Shafiyahijab Syar’i.Keywords: AEC, ASEAN, e-commerce, Shafiyahijab Syar’i.